2020
DOI: 10.21203/rs.3.rs-33094/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bigger doesn’t mean bolder: Behavioral variation of four wild rodent species to novelty and predation risk following a fast-slow continuum

Abstract: Background: Understanding how wild species respond to novel situations with associated risk can provide valuable insights for inter-specific behavioral variation and associations with pace-of-life (POL). Rodents, a globally distributed and diverse taxonomic group, have been the subjects of countless studies emulating risky situations. Controlled laboratory experiments with a focus on wild-caught species provide the opportunity to test fine-scale behavioral responses to contexts of risk with ecological implica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…This suggests that abundance was more important than size in prey selection (Charter et al, 2007). It has also been suggested that owls prefer smaller rodents to heavier ones (Trejo & Guthmann, 2003), probably because smaller species spend more time exploring and foraging, hence being more exposed (Best et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that abundance was more important than size in prey selection (Charter et al, 2007). It has also been suggested that owls prefer smaller rodents to heavier ones (Trejo & Guthmann, 2003), probably because smaller species spend more time exploring and foraging, hence being more exposed (Best et al, 2020).…”
Section: Resultsmentioning
confidence: 99%